[tex]przyklad \: {4}^{ - 2} \times {4}^{2} = {4}^{ - 2 + 2} = {4}^{0} = 1[/tex]
[tex]zadane \\ a) {3}^{5} \times {3}^{ - 8} = \: \: \: \: \: \: [/tex]
[tex]b)( \frac{5}{7} )^{ - 6} \times ( \frac{5}{7} ) {}^{4} = [/tex]
[tex]c)(2 \frac{1}{3} ) {}^{5} \times (2 \ \frac{1}{3} ){}^{ - 3} = [/tex]
[tex]d) {3}^{4} \times {3}^{ - 3} = [/tex]
[tex]e) {2}^{3} \times {2}^{5} \times {2}^{ - 2} \times {2}^{2} = [/tex]
Proszę o pomoc


Odpowiedź :

Obliczenia

[tex]3^5\cdot3^{-8}=3^{5+(-8)}=3^{5-8}=3^{-3}=(\frac{1}{3})^3=\frac{1}{27}\\\\(\frac{5}{7})^{-6}\cdot(\frac{5}{7})^4=(\frac{5}{7})^{-6+4}=(\frac{5}{7})^{-2}=(\frac{7}{5})^2=\frac{49}{25}=1\frac{24}{25}\\\\(2\frac{1}{3})^5\cdot(2\frac{1}{3})^{-3}=(2\frac{1}{3})^{5+(-3)}=(2\frac{1}{3})^{5-3}=(2\frac{1}{3})^2=(\frac{7}{3})^2=\frac{49}{9}=5\frac{4}{9}[/tex]

[tex]3^4\cdot3^{-3}=3^{4+(-3)}=3^{4-3}=3^1=3\\\\2^3\cdot2^5\cdot2^{-2}\cdot2^2=2^{3+5+(-2)+2}=2^{10-2}=2^8=256[/tex]